Mesocolic desmoid tumour presenting as an acute abdomen - Ramasamy, Prabhu; A R, Fadli; Suboh, Roslina; Mat Hassan, Mohd. Zailani; Md Nor, Azmi (2010)
Mesenteric fibromatosis (MF) is a subgroup of intraabdominal desmoid tumour and is a rare neoplasm. MF is a locally aggressive fibroconnective tissue neoplasm that frequently recurs after excision but does not metastasize. There is a high association of mesenteric fibromatosis with previous trauma, hormonal imbalance and Gardner's syndrome. This tumour is commonly found in the mesentery of the small bowel and usually has an insidious clinical presentation. Surgical removal with segments of bowel remains the treatment of choice. We report a case of Mesenteric fibromatosis (MF) in the mesocolon presenting as an acute abdomen.